The hidden biotic face of microbialite morphogenesis - a case study from Laguna de Los Cisnes, southernmost Patagonia (Chile) - Pollier, Clement G. L.; Guerrero, Alejandro N.; Rabassa, Jorge; Ariztegui, Daniel (My University, 2024)
Microbialites provide geological evidence into Earth's early ecosystems, recording long-standing interactions between co-evolving life and the environment. Yet, after more than 100 years of research, the complex interplay between environmental and biological forces involved in microbialite growth is still debated. Laguna de Los Cisnes, located in Chilean Tierra del Fuego, Patagonia, provides a unique opportunity to study these interactions. This lake, which became ice-free around 10 000 years ago, features carbonate microbialites developed by algal-microbial communities. Macroscopically, the organo-sedimentary deposits exhibit a consistent primary crater-like architecture, showcasing macrostructural variations such as dish-shaped, hemispherical, columnar and lenticular morphologies. This study explores the environmental and biological factors shaping microbialite macrostructure by analysing the distribution of dominant morphotypes across the basin. Concurrently, it examines the internal mesostructure and microstructure of microbialites in association with prevailing algal-microbial communities. The incremental development of these communities contributes to the distinct crater-like morphology observed in microbialites from Laguna de Los Cisnes. The mineral encrustation of the green alga Percursaria percursa emerges as a primary driver of lithification, evidenced by the preservation of microfossils within the microstructure of the microbialites. Simultaneously, physical environmental factors, including waves, Langmuir cells and accommodation space influence the location of the algal-microbial carbonate factory, determining the spatial distribution and temporal succession of different crater architecture variants. Laguna de Los Cisnes, hosting well-preserved subfossil outcrops and living microbialites, serves as a remarkable living laboratory for understanding microbialite morphogenesis. This study contributes to a novel model that captures the fundamental role of algal-microbial communities in determining the primary macrostructural architecture of microbialites before environmental factors come into play, merely reshaping this architecture into different morphotypes.
Keywords: algal-microbial communities; lacustrine environment; macrostructure; microbialites; patagonia